Abnormal uterine bleeding in perimenopause. (3rd September 2017) - Goldstein, S. R.; Lumsden, M. A.
Abstract: Abnormal uterine bleeding is one of the commonest presenting complaints encountered in a gynecologist's office or primary-care setting. The wider availability of diagnostic tools has allowed prompt diagnosis and treatment of an increasing number of menstrual disorders in an office setting. This White Paper reviews the advantages and disadvantages of transvaginal ultrasound, blind endometrial sampling and diagnostic hysteroscopy. Once a proper diagnosis has been established, appropriate therapy may be embarked upon. Fortunately, only a minority of such patients will have premalignant or malignant disease. When bleeding is sufficient to cause severe anemia or even hypovolemia, prompt intervention is called for. In most of the cases, however, the abnormal uterine bleeding will be disquieting to the patient and significantly affect her 'quality of life'. Sometimes, reassurance and expectant management will be sufficient in such patients. Overall, however, in cases of benign disease, some intervention will be required. The use of oral contraceptive pills especially those with a short hormone-free interval, the insertion of the levonorgestrel intrauterine system, the incorporation of newer medical therapies including antifibrinolytic drugs and selective progesterone receptor modulators and minimally invasive treatments have made outpatient therapy increasingly effective. For others, operative hysteroscopy and endometrial ablation are proven therapeutic tools to provide both long- and short-term relief of abnormal uterine bleeding, thus avoiding, or deferring, hysterectomy.